Sulfonated Schiff base immobilized on magnetite-chitosan as an efficient nanocatalyst for the synthesis of xanthene derivatives - Mohammadhossein Alijafari Taheri; Moslem Setoodehkhah; Mohsen Moradian (Scientific Reports)
Abstract The present study aims to develop and enhance a magnetic heterogeneous catalyst with a core-shell structure, Fe3O4@CS/SSB (Fe3O4@Chitosan-Salicylaldehyde-5-sulfonate), by immobilizing a chitosan-based Schiff base complex on the surface of magnetite. Chitosan, a low-cost, biodegradable, and biocompatible polymer with a suitable chemical structure such as the NH₂ functional group plays a significant role in heterogeneous catalytic systems. In this research, the Schiff base was synthesized through the condensation of a sulfonated aromatic aldehyde (salicylaldehyde) with the amine group of chitosan, forming a magnetic nanocatalyst with acidic properties. The catalyst was characterized using various analytical techniques, including XRD, FT-IR, VSM, TGA, DLS, FE-SEM, EDX, and TEM. The catalytic performance of the nanomagnetic catalyst was evaluated in the synthesis of 14-aryl-14-H-dibenzo[a, j]xanthenes and 12-aryl-9,9-dimethyl-8,9,10,12-tetrahydrobenzo[a]xanthen-11-ones via a one-step condensation reaction of dimedone, 2-naphthol, and aryl aldehydes in ethanol. The progress of the reaction was monitored using thin-layer chromatography (TLC). The xanthenes derivatives were characterized by FT-IR, 1H NMR, and 13C NMR analyses. Ultimately, it was observed that the catalyst could be reused multiple times without significant loss of catalytic activity.